A challenging entity: multiple sclerosis or collagen tissue disorders: A case series of 6 patients - Raida Ben Salah; Yosra Cherif; Feten Frikha; Chifa Dammak; Mouna Snoussi; Moez Jallouli; Sameh Marzouk; Mhiri Chokri; Zouhir Bahloul (Babol University of Medical Sciences, 2017)
Background: Multiple sclerosis and other demyelinating processes are sometimes difficult to differentiate from the neurological involvement in autoimmune diseases. Distinguishing multiple sclerosis from other lesions due to autoimmune diseases is crucial to avoid unsuitable or delayed treatments. Methods: Charts of 6 patients diagnosed with mimicking multiple sclerosis between 1996 and 2014 were retrospectively assessed. Results: The mean age at diagnosis was 35±7 years. The most commonly neurological manifestation at onset was paraparesis due to transverse myelopathy and uni/bilateral optic neuropathy. All our patients suffered from recurrent episodes of optic neuritis with a mean lag time of 12 months. Other initial presenting neurological manifestations in our patients included ataxic gait and pyramidal syndrome. Systemic symptoms occurred a long time before or after their initial neurological presentation. All patients had numerous T2 hyperintense lesions in the periventricular white matter and spinal cord with contrast enhancement. The antibodies tests revealed the presence of significant amounts of anti-nuclear antibodies. The anti-phospholipid antibodies were negative in all patients. All patients were treated with corticosteroid therapy and neurological features were cleared in all cases. Conclusion: Multiple sclerosis, other myelitis and optic neuritis, are sometimes difficult to differentiate from CNS involvement in autoimmune disease. Indeed, the clinical presentation, immunological profile and MRI lesions may be similar.